"Some Mother's Child Has Gone Astray": Neuroscientific Approaches to a Therapeutic Jurisprudence Model of Juvenile Sentencing. (1st July 2021) - Perlin, Michael L.; Lynch, Alison J.
Abstract : There is a robust body of evidence that tells us that the juvenile brain is not fully developed by age 18, and this evidence should and does raise important questions about the sentencing of juveniles in criminal cases. This evidence, though, must be considered in the context of public opinion (about certain juvenile crimes that have been subject to saturation publicity) in the context of judges' decisionmaking (where such judges do not want to be perceived as "soft on crime"). The conflict between what we now know and what (false) "ordinary common sense" demands (in the way of enhanced punishments) flies squarely in the face of therapeutic jurisprudence precepts. If the legal process is to seek to maximize psychological well‐being and if it is to coincide with an "ethic of care, " then, it is necessary for those involved in the criminal justice system to speak publicly about this topic, and to "call out" those – be they elected politicians, editorial writers and commentators in the conservative media, or judges – who urge retributive and punitive sentences for adolescents and children. In this paper, we will first give a brief overview about the current neuroscientific findings about juvenile brain development in the context of criminal behavior, and then discuss the current sentencing standards and regulations that are in place. Then, we will discuss the impact of therapeutic jurisprudence as a framework for advocating for juvenile clients, in order to maximize and preserve their psychological well‐being and to mitigate trauma. Finally, we will offer recommendations for how experts can work with attorneys who are presenting sentencing arguments, in order to make the most comprehensive, scientifically persuasive case for leniency in juvenile sentencing. Key Points for the Family Court Community: It is well‐settled that the juvenile brain is not fully developed by age 18. Transfer to adult court appears to be counterproductive: transferred youths are more likely to reoffend, and to reoffend more quickly and more often, than those retained in the juvenile justice system. Even when an individual turns the age of 18 and is considered to be a legal adult, his brain still has years of development and maturity ahead of it. We must think about issues such as race and class in considering the sentencing of juveniles. We must consider therapeutic jurisprudence principles in the context of the fact that certain juvenile crimes have been subject to saturation publicity, creating intense pressure of judges who do not want to be perceived as being "soft on crime." Our current juvenile sentencing system in no way values psychological health, " nor advances an "ethic of care, " both essential in a therapeutic jurisprudence analysis.